2008
DOI: 10.1007/s11581-008-0203-6
|View full text |Cite
|
Sign up to set email alerts
|

A conductivity study of polyelectrolytes based on 4-vinyl pyridine and butylmethacrylate

Abstract: In this paper, the chain flexibility of P4-VP was tried to increase by lowering its glass transition temperature (T g ) and by increasing its amorphous region by copolymerizing with butyl methacrylate. The copolymers were prepared in five different feed molar ratios to optimize the required properties such as higher room temperature conductivity and film-forming capacity. The conductivity and conduction behavior of the copolymers, as well as their hydrochloride and hydrobromide salts, have been reported. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Even though the overall charge carrier number was reduced with the rise of the HMA content, the copolymer conductivity was increased due to the significant lowering of T g . In a similar manner the copolymerization of N -vinylpyridine with HMA resulted in the improvement of polymer flexibility and as a consequence in the decrease of the T g of the copolymers . It should be mentioned that such improvement of ionic conductivity is passing through a maximum; i.e.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Even though the overall charge carrier number was reduced with the rise of the HMA content, the copolymer conductivity was increased due to the significant lowering of T g . In a similar manner the copolymerization of N -vinylpyridine with HMA resulted in the improvement of polymer flexibility and as a consequence in the decrease of the T g of the copolymers . It should be mentioned that such improvement of ionic conductivity is passing through a maximum; i.e.…”
Section: Introductionmentioning
confidence: 81%
“…Such approach helps to decrease the ion–ion interaction in PIL by the introduction of the neutral side chains and simultaneously to increase the flexibility of the polyelectrolyte chain or to reduce the copolymer’s glass transition temperature ( T g ). This solution was successfully applied by Elabd and Dutta . When 1-[2-methacryloyloxy)ethyl]-3-butylimidazolium tetrafluoroborate was copolymerized with hexyl methacrylate (HMA), the bulk ionic conductivity of the nonionic–ionic copolymer was increased by more than 1 order of magnitude .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be classified as acid-base reactive [13] polyacids or acid-like molecules and base centers of the polymers [14][15][16][17][18]. Hirao et al [19] reported the conductivity study of molten salt of N-vinylimidazolium tetrafluoroborate and its polymer.…”
Section: Introductionmentioning
confidence: 99%
“…12 Compared to pure PVP, PVPBM showed improved thermal stability and higher conductivity. 13 It was utilised for the fabrication of humidity sensors, 14 which exhibited quick response, very small hysteresis and high chemical stability. It offers important advantages for the fabrication of composites using colloidal methods.…”
Section: Introductionmentioning
confidence: 99%